Sistem Pendukung Keputusan Pemilihan Peserta FLS2N SMAN 1 Perbaungan Menggunakan Metode MABAC - Zulkarnain Zulkarnain; Yasir Hasan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2021)
Selection of students of SMAN 1 Perbaungan to find out results that are balanced with the training that has been carried out at the school. SMAN 1 The previous comparison was not good, because there were still students or students who were dissatisfied with the results and there was an unrealistic impression. Besides that, SMAN 1 Perbaungan also had difficulty processing student data because there were only 8 students selected. For this reason, students and SMAN 1 Perbaungan want a more systematic selection process with the help of computerized calculation of decision support systems. The selection process for FLS2N SMAN 1 Perbaungan participants uses the MABAC method. The adoption of a decision support system and the MABAC method can help SMAN 1 Perbaungan in selecting FLS2N participants both systematically and with more realistic ranking results